Point-of-Care Ultrasound Use by EMS Providers in Out-of-Hospital Cardiac Arrest. Issue 1 (7th February 2022) - Kreiser, Michael A.; Hill, Brieanna; Karki, Dikchhya; Wood, Elke; Shelton, Ryan; Peterson, Jodi; Riccio, John; Zapata, Isain; Khalil, Paul A.; Gubler, Dean; LaPorta, Anthony J.; Roosevelt, Genie E.; et al.
Abstract: Aim: Paramedics received training in point-of-care ultrasound (POCUS) to assess for cardiac contractility during management of medical out-of-hospital cardiac arrest (OHCA). The primary outcome was the percentage of adequate POCUS video acquisition and accurate video interpretation during OHCA resuscitations. Secondary outcomes included POCUS impact on patient management and resuscitation protocol adherence. Methods: A prospective, observational cohort study of paramedics was performed following a four-hour training session, which included a didactic lecture and hands-on POCUS instruction. The Prehospital Echocardiogram in Cardiac Arrest (PECA) protocol was developed and integrated into the resuscitation algorithm for medical non-shockable OHCA. The ultrasound (US) images were reviewed by a single POCUS expert investigator to determine the adequacy of the POCUS video acquisition and accuracy of the video interpretation. Change in patient management and resuscitation protocol adherence data, including end-tidal carbon dioxide (EtCO2 ) monitoring following advanced airway placement, adrenaline administration, and compression pauses under ten seconds, were queried from the prehospital electronic health record (EHR). Results: Captured images were deemed adequate in 42/49 (85.7%) scans and paramedic interpretation of sonography was accurate in 43/49 (87.7%) scans. The POCUS results altered patient management in 14/49 (28.6%) cases. Paramedics adhered to EtCO2 monitoring in 36/36 (100.0%) patients with an advanced airway, adrenaline administration for 38/38 (100.0%) patients, and compression pauses under ten seconds for 36/38 (94.7%) patients. Conclusion: Paramedics were able to accurately obtain and interpret cardiac POCUS videos during medical OHCA while adhering to a resuscitation protocol. These findings suggest that POCUS can be effectively integrated into paramedic protocols for medical OHCA.